Introduction to the thematic issue: Recognition of women leaders in Science. Issue 24 (December 2022) - Conran, Nicola; Lambert, Muriel; Turner, Nancy D
This thematic issue of Experimental Biology and Medicine is dedicated to the incredibly important contributions made by women leaders in the biomedical sciences throughout recent history. Scientists from many disciplines have contributed papers, both original research and state of the art reviews, to demonstrate the type of work being performed every day by women leaders committed to advancing scientific knowledge in their respective fields of specialization. In this introduction, we provide readers with a brief highlight of the information to be found in the invited papers.